wiishesssss
New member
- Joined
- Nov 5, 2006
- Messages
- 26
7r ^ 2 - 3r - 6 = 0
So i divided by 7 ..
so i did 7r ^ 2 / 7 , -3r / 7 , -6/7 , and 0/7
so now i have ..
r ^ 2 - 3r/7 = 6/7
(b/2) ^ 2 = ( (3/7) / 2 ) ^ 2 = (3/14) ^ 2
r ^ 2 - 3/7 + (3/14) ^ 2 = 6/7 (3/14) ^ 2
now i know
r ^ 2 - 3/7 + (3/14) ^ 2 is a perfect square trinomial
(r - 3/14) ^ 2
If anyone can help me from that point on i would appreciate it.
So i divided by 7 ..
so i did 7r ^ 2 / 7 , -3r / 7 , -6/7 , and 0/7
so now i have ..
r ^ 2 - 3r/7 = 6/7
(b/2) ^ 2 = ( (3/7) / 2 ) ^ 2 = (3/14) ^ 2
r ^ 2 - 3/7 + (3/14) ^ 2 = 6/7 (3/14) ^ 2
now i know
r ^ 2 - 3/7 + (3/14) ^ 2 is a perfect square trinomial
(r - 3/14) ^ 2
If anyone can help me from that point on i would appreciate it.